Tirofiban in acute coronary syndromes. (March 2005) - Menozzi, Alberto; Merlini, Piera Angelica; Ardissino, Diego
Acute coronary syndromes represent a major health problem in terms of incidence and mortality. Intracoronary platelet-rich thrombi may develop in response to plaque rupture, and are involved in the pathogenesis of all acute coronary syndromes. The glycoprotein IIb/IIIa receptor, a platelet surface integrin, plays a key role in platelet aggregation once it has been activated by specific ligands. The development of glycoprotein IIb/IIIa inhibitors has revolutionized the management of acute coronary syndromes. Tirofiban is one of three parenteral glycoprotein IIb/IIIa inhibitors in clinical use, and many trials have demonstrated its clinical efficacy and low rate of adverse effects in patients with non-ST-segment elevation acute coronary syndrome. This article reviews the data concerning its use in the clinical settings of acute coronary syndromes and percutaneous coronary angioplasty, and discusses its benefits in different treatment strategies and in association with other drugs. In particular, the role of early, upstream tirofiban coupled with early aggressive revascularization in the management of high-risk non-ST-segment elevation acute coronary syndromes is emphasized.